A Rare Presentation of Sciatic Palsy Due to Hematoma After Use of the Kocher-Langenbeck Approach to the Acetabulum. Issue 1 (January 2015) - Rog, Dominik; Basmajian, Hrayr G.
Abstract : Case: A delayed sciatic palsy caused by compression due to hematoma formation is a rare complication of total hip arthroplasty. We report the case of a twenty-seven-year-old man who underwent open reduction and internal fixation of transverse and posterior wall acetabular fractures with posterior hip dislocation and had development of a delayed sciatic palsy due to the formation of a hematoma five days after the procedure. Conclusion: A patient who presents with a delayed-onset sciatic palsy with signs and symptoms of a hematoma after an acetabular surgery represents a surgical emergency. Early recognition and urgent decompression offers the best chance of nerve recovery.